Syndecan-4–/– Mice Have Smaller Muscle Fibers, Increased Akt/mTOR/S6K1 and Notch/HES-1 Pathways, and Alterations in Extracellular Matrix Components - Rønning, Sissel Beate; Carlson, Cathrine Rein; Aronsen, Jan Magnus; Pisconti, Addolorata; Høst, Vibeke; Lunde, Marianne; Liland, Kristian Hovde; Sjaastad, Ivar; Kolset, Svein Olav; Christensen, Geir; Pedersen, Mona Elisabeth (Frontiers in Cell and Developmental Biology, 2020)
Background: Extracellular matrix (ECM) remodeling is essential for skeletal muscle development and adaption in response to environmental cues such as exercise and injury. The cell surface proteoglycan syndecan-4 has been reported to be essential for muscle differentiation, but few molecular mechanisms are known. Syndecan-4-/- mice are unable to regenerate damaged muscle, and display deficient satellite cell activation, proliferation, and differentiation. A reduced myofiber basal lamina has also been reported in syndecan-4-/- muscle, indicating possible defects in ECM production. To get a better understanding of the underlying molecular mechanisms, we have here investigated the effects of syndecan-4 genetic ablation on molecules involved in ECM remodeling and muscle growth, both under steady state conditions and in response to exercise. Methods: Tibialis anterior (TA) muscles from sedentary and exercised syndecan-4-/- and WT mice were analyzed by immunohistochemistry, real-time PCR and western blotting. Results: Compared to WT, we found that syndecan-4-/- mice had reduced body weight, reduced muscle weight, muscle fibers with a smaller cross-sectional area, and reduced expression of myogenic regulatory transcription factors. Sedentary syndecan-4-/- had also increased mRNA levels of syndecan-2, decorin, collagens, fibromodulin, biglycan, and LOX. Some of these latter ECM components were reduced at protein level, suggesting them to be more susceptible to degradation or less efficiently translated when syndecan-4 is absent. At the protein level, TRPC7 was reduced, whereas activation of the Akt/mTOR/S6K1 and Notch/HES-1 pathways were increased. Finally, although exercise induced upregulation of several of these components in WT, a further upregulation of these molecules was not observed in exercised syndecan-4-/- mice. Conclusions: Altogether our data suggest an important role of syndecan-4 in muscle development.